2017
DOI: 10.2174/1570159x15666170329091935
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-engaged Mechanisms of Nongenomic Action of Neurosteroids

Abstract: Background: Neurosteroids form the unique group because of their dual mechanism of action. Classically, they bind to specific intracellular and/or nuclear receptors, and next modify genes transcription. Another mode of action is linked with the rapid effects induced at the plasma membrane level within seconds or milliseconds. The key molecules in neurotransmission are calcium ions, thereby we focus on the recent advances in understanding of complex signaling crosstalk between action of neurosteroids and calciu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 138 publications
(142 reference statements)
1
9
0
Order By: Relevance
“…It is also well known that, over the GABA A ‐R, AP may regulate neuroendocrine and/or neuroprotective processes via interactions with various other receptors such as the L‐type Ca 2+ channels, the pregnane X receptor, the liver X receptor, the nicotinic and serotonin type 3 receptors and membrane progesterone G‐coupled protein receptors (mPR), including mPRδ, mPRα and mPRβ . Altogether, these data suggest that the ANS‐evoked structure‐based neuroprotective and/or proliferation‐promoting effects identified in the present study may involve selective interactions with various receptors, including ligand‐gated ion channels and/or G‐coupled protein receptors regulating neuroendocrine and/or neurophysiological activities . In support of this idea, previous studies have shown that neuroblastoma SH‐SY5Ycells express various receptors, including sigma and NMDA receptors, which mediate certain effects of neurosteroids …”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…It is also well known that, over the GABA A ‐R, AP may regulate neuroendocrine and/or neuroprotective processes via interactions with various other receptors such as the L‐type Ca 2+ channels, the pregnane X receptor, the liver X receptor, the nicotinic and serotonin type 3 receptors and membrane progesterone G‐coupled protein receptors (mPR), including mPRδ, mPRα and mPRβ . Altogether, these data suggest that the ANS‐evoked structure‐based neuroprotective and/or proliferation‐promoting effects identified in the present study may involve selective interactions with various receptors, including ligand‐gated ion channels and/or G‐coupled protein receptors regulating neuroendocrine and/or neurophysiological activities . In support of this idea, previous studies have shown that neuroblastoma SH‐SY5Ycells express various receptors, including sigma and NMDA receptors, which mediate certain effects of neurosteroids …”
Section: Discussionsupporting
confidence: 81%
“…79,80 Altogether, these data suggest that the ANS-evoked structure-based neuroprotective and/or proliferation-promoting effects identified in the present study may involve selective interactions with various receptors, including ligand-gated ion channels and/or Gcoupled protein receptors regulating neuroendocrine and/or neurophysiological activities. [81][82][83] In support of this idea, previous studies have shown that neuroblastoma SH-SY5Ycells express various receptors, including sigma and NMDA receptors, which mediate certain effects of neurosteroids. [84][85][86][87][88] In conclusion, the present study, which demonstrates the identification of novel and efficient analogues of the key neuromodulator AP, also opens interesting and promising perspectives with respect to using neurosteroids for the development of structure-based selective and effective strategies against various neuroendocrine and/or neurodegenerative disorders.…”
Section: Discussionmentioning
confidence: 80%
“…These compounds and their synthetic analogs are mainly known as potent modulators of GABA A Rs (Chen et al, 2019) and N-methyl-D-aspartate receptors (NMDARs) (Burnell et al, 2019), respectively. Neurosteroids and their synthetic analogs (neuroactive steroids, NAS) have been extensively studied during last three decades as they modify neuronal activity and thus brain function via a fast, non-genomic action (Rebas et al, 2017), by acting as allosteric modulators of various ligandgated ion channels, including GABA A R and GlyR. In brief, NS and NAS are effective modulators of GABA A R-induced chloride current (I GABA ) and their modulatory action is dependent on their structure and subtype (for a review, see: Majewska et al, 1988;Wu et al, 1990;Belelli and Lambert, 2005;Korinek et al, 2011;King, 2013;Zorumski et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Here, we will review the opposing effects of neurosteroids on GABA A and NMDA receptors [97][98][99]. Neurosteroids also act on several other ion channel receptors, including glycine, AMPA and sigma receptors, which have recently been reviewed by Rebas et al [100].…”
Section: Signalling Functions Of Neurosteroidsmentioning
confidence: 99%